KORELASI LINGKAR SKROTUM TERHADAP KUANTITAS DAN KUALITAS SEMEN PEJANTAN SAPI PERAH FRIESIAN HOLSTEIN DI BBIB SINGOSARI KABUPATEN MALANG - Muhammad Yofi Puji Santoso (AVES: Jurnal Ilmu Peternakan, 2022)
This research aims to determine whether there is a correlation between the quantity of scrotal circumference and quality of semen from Friesian Holstein cattle at the Singosari Center for Artificial Insemination, Malang. The sample used for the fresh semen of Friesian Holstein cattle was 5 cows. The variables observed were scrotal circumference, semen volume, acidity (pH), spermatozoa motility, spermatozoa abnormalities, and spermatozoa concentration. The data were analyzed by using Ms. Excel, and also showed a correlation between scrotal circumference and semen volume r = 0,07, scrotal circumference with pH r = -0,15, scrotal circumference with spermatozoa motility r = 0,73, scrotal circumference with abnormal spermatozoa r = -0,72, scrotal circumference with spermatozoa concentration r = 0,03. Thus, the results obtained were very low correlation between scrotal circumference with semen volume and spermatozoa concentration, strong correlation between scrotal circumference and spermatozoa motility, and no correlation between scrotal circumference with pH and spermatozoa abnormality